Characterization and classification of the provitamin A carotenoids of deep yellow-fleshed bitter yam (Dioscorea dumetorum) varieties - Alamu, Emmanuel Oladeji; Maziya-Dixon, B.B.; Ferede-Menkir, R.; Popoola, I.; Asiedu, Robert; Gondwe, T.N.P. (Science and Education Publishing Co., Ltd., 2016)
Twenty-two genotypes of deep yellow fleshed D. dumetorum were analysed for carotenoids using High Performance Liquid Chromatography (HPLC) and for similarities in their provitamin A characteristics using Cluster Analysis (CA). The contribution of each carotenoid to provitamin A content was investigated through correlation and regression analysis. Seven of the genotypes fell within the low provitamin A cluster with values from 2.26 µg g-1 to 7.74 µg g-1. Twelve genotypes were in the intermediate cluster with values between 8.56 µg g-1 and 11.20 µg g-1. Three genotypes were within the high cluster with values between 10.13 µg g-1 and 14.00 µg g-1. Trans-β-carotene-5,8 epoxide was a significant predictor (β1 = 0.773, p < 0.005) of provitamin A content of the D. dumetorum while trans-β-carotene was not a significant predictor (β2 = 0.593, p > 0.05).